2017
DOI: 10.1088/1361-6668/aa902f
|View full text |Cite
|
Sign up to set email alerts
|

Generating mixed morphology BaZrO3artificial pinning centers for strong and isotropic pinning in BaZrO3–Y2O3double-doped YBCO thin films

Abstract: High concentration artificial pinning centers (APCs), such as BaZrO3 nanorods (BZO 1D APCs) aligned along the c-axis of the high temperature superconductor YBa2Cu3O7 (YBCO) can provide strong pinning of magnetic vortices and are desirable for applications in high magnetic fields. Unfortunately, in YBCO films with single-doping (SD) of BZO 1D APCs, a monotonic decreasing superconducting Tc and critical current density Jc(H) with BZO doping has been observed due to strain field overlap at high-concentration perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Recently, the hybrid pinning consisting of multiple types of pinning centers has been investigated for further control of vortex pinning, [21][22][23][24][25] where combination of nanorods and nanoparticles is one of the most effective hybrid pinning systems. In the YBCO tapes containing BSO nanorods and Y 2 O 3 nanoparticles, the nanorods have worked as strong c-axis correlated pinning centers to mainly determine J c for B//c, while the nanoparticles have improved the J c in high magnetic field and suppressed the J c anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the hybrid pinning consisting of multiple types of pinning centers has been investigated for further control of vortex pinning, [21][22][23][24][25] where combination of nanorods and nanoparticles is one of the most effective hybrid pinning systems. In the YBCO tapes containing BSO nanorods and Y 2 O 3 nanoparticles, the nanorods have worked as strong c-axis correlated pinning centers to mainly determine J c for B//c, while the nanoparticles have improved the J c in high magnetic field and suppressed the J c anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…Jha et al reported reduced J c anisotropy from 180% to 80% with 3 areal% of Y 2 O 3 and 3 vol.% BSO concentrations in YBCO as compared to its singly-doped (SD) counterpart (with BSO only) at 65 K and 1 T [15]. Similarly, Chen et al observed reduced anisotropy in BZO + Y 2 O 3 DD films of varying BZO concentrations of 2-6 vol.% and 3 vol.% of Y 2 O 3 [4]. J c anisotropy as low as 18% has been observed at 65 K and 9 T by Gautam et al in YBCO DD films containing 2 vol.…”
Section: Introductionmentioning
confidence: 90%
“…The c-axis-aligned one-dimensional artificial pinning centers (1D-APCs), such as nanorods of BaZrO 3 (BZO), BaSnO 3 (BSO), BaHfO 3 (BHO), and YBa 2 (Nb/Ta)O 6, in high temperature superconducting (HTS) REBaCu 3 O 7-x (RE = Y, Gd, Sm) films provide strong correlated pinning at B//c-axis [1][2][3][4][5][6][7][8][9][10]. However, the strain field originated from the lattice mismatch at the 1D-APC/REBCO interface could result in reduced superconducting transition temperature (T c ) and critical current density (J c ) at temperatures close to T c [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various APCs of different morphologies, including c-axis aligned one-dimensional nanorods (1D-APCs), ab-plane aligned twodimensional planar defects (2D-APCs), and three-dimensional nanoparticles (3D-APCs) have been reported through the addition of secondary dopants like BaZrO 3 (BZO), BaHfO 3 (BHO), BaSnO3 (BSO), YBa2(Nb/Ta)O6, Y2O3, etc. in YBCO (or other rare-earth variation of YBCO) to form APC/YBCO nanocomposites films [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%